Such kindness : a novel [large type] - Dubus, Andre, III, 1959- (Thorndike Press large print top shelf., 2023)
"Tom Lowe's identity and his pride are invested in the work he does with his back and his hands. He designed and built his family's dream home, working extra hours to pay off the adjustable rate mortgage he took on the property, convinced he is making every sacrifice for the happiness of his wife and son. Until, in a moment of fatigued inattention, shingling a roof in too-bright sunlight, he falls. In constant pain, addicted to painkillers at the cost of his relationships with his wife and son, Tom slowly comes to realize that he can never work again. If he is not a working man, who is he? He is not, he believes, the kind of person who lives in subsidized housing, though that is where he has ended up. He is not the kind of person who hatches a scheme to commit convenience-check fraud, together with neighbors he considers lowlifes, until he finds himself stealing his banker's trash. Who is Tom Lowe, and who will he become? Can he find a way to reunite hands and heart, mind and spirit, to be once again a giver and not just a taker, to forge a self-acceptance deeper than pride? Andre Dubus III's soulful cast includes Trina, the struggling mom next door who sells her own plasma to get by; Dawn, the tough-talking owner of the local hairdressing salon; Jamie, a well-meaning pothead college student ready to stick it to "the man"; and a mix of strangers and neighbors who will never know the role they played in changing a life. To one man's painful moral journey, Dubus brings compassion with an edge of dark absurdity, forging a novel as absorbing as it is profound"--